Gadara, Jordanien. Das "Gadara Region Project" - Häser, Jutta (e-Forschungsberichte des DAI, 2017)
An essential part of any excavation is documentation, because the excavation of a site results always in irreversible destruction. Since 2012, the “Gadara Region Project”, based on Tall Zirāʿa and in the Wādī al-ʿArab, has focused on publishing the results of surveys and excavations gathered in eighteen seasons from 2001 to 2011. The various volumes of the series “Gadara Region Project” will be available as an Online-Publication in the English language. The first volume serves as an introduction to the stratigraphy of Tall Zirāʿa and its geographical setting within the Wādī al-ʿArab.